Sacrality and Vindication: Programmatic Elements and Meaning of Civil War in Valerius Flaccus - Arriaga Benítez, Juan Manuel (2024)
Valerius Flaccus adopts the traditional conception that dictated how political and moral decadence began since human beings violated the sacredness of the sea; however, the poet surreptitiously communicates that the irruption of a ship on the oceanic roads constitutes a vindication and that decline is actually raher a civil war as an instrument of the alternation of power. It is in light of this subtext that his epic constructs a paradox that oscillates between the disruptive and promoting roles of that instrument that symbolizes them, the Argo ship. This mythical navigation is at the heart of this discussion and the programmatic implications of what the poem contains in its first book invite the reader to reflect on the true meaning of the alleged oceanic desacralization, the alternation of empires in power and the origin of civil discord.